2018
DOI: 10.1111/1751-7915.13259
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Heterobasidion occidentale transcriptomes reveals candidate genes and DNA polymorphisms for virulence variations

Abstract: SummaryCharacterization of genes involved in differentiation of pathogen species and isolates with variations of virulence traits provides valuable information to control tree diseases for meeting the challenges of sustainable forest health and phytosanitary trade issues. Lack of genetic knowledge and genomic resources hinders novel gene discovery, molecular mechanism studies and development of diagnostic tools in the management of forest pathogens. Here, we report on transcriptome profiling of Heterobasidion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In addition to RNA-seq, genome-wide association analysis (GWAS) was also used to identify the SNPs and the candidate genes significantly associated with Norway spruce susceptibility to H. parviporum ( Mukrimin et al, 2018 ). A previous study characterized a large set of secreted proteins as candidate effectors in the H. occidentale transcriptome ( Liu et al, 2018 ). Effectors from pests/pathogens have capacity to suppress the NLR-dependent host resistance by directly binding to the NLRs or other molecular mechanisms ( Derevnina et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to RNA-seq, genome-wide association analysis (GWAS) was also used to identify the SNPs and the candidate genes significantly associated with Norway spruce susceptibility to H. parviporum ( Mukrimin et al, 2018 ). A previous study characterized a large set of secreted proteins as candidate effectors in the H. occidentale transcriptome ( Liu et al, 2018 ). Effectors from pests/pathogens have capacity to suppress the NLR-dependent host resistance by directly binding to the NLRs or other molecular mechanisms ( Derevnina et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq reads were first filtered by Trimmomatic 1 with default setting at Illuminaclip: TruSeq3-PE.fa:2:30:10, Leading: 3, Trailing: 3, Slidingwindow: 4:15, Minlen: 36 ( Bolger et al, 2014 ). To detect H. occidentale genes expressed in Hemlock stem tissues, RNA-seq reads were mapped to a reference transcriptome assembled from RNA-seq reads of H. occidentale mycelium cultures in a previous study ( Liu et al, 2018 ). Mapping was performed using CLC Genomics Workbench (v5.5) with minimum length fraction = 0.9, and minimum similarity fraction = 0.98.…”
Section: Methodsmentioning
confidence: 99%
“…They found that HIRHG was up-regulated during infection and maybe important for the pathogen to grow in a pectin containing environment. Liu et al 37 compared the transcriptomes of two different H. occidentale isolates grown on apple fruits. Their results suggest that the capacity of H. occidentale to colonize apple fruit correlated with the expression of potential carbohydrate active enzyme genes 37 .…”
Section: Discussionmentioning
confidence: 99%
“…They are also capable of both necrotic and saprotrophic growth. H. irregulare was the first Heterobasidion species to be characterized for complete genome sequence ( Olson et al, 2012 ; Garbelotto and Gonthier, 2013 ), and thereafter also genomes of H. annosum ( Sillo et al, 2015 ; Choi et al, 2017 ), H. occidentale ( Liu et al, 2018 ), and H. parviporum ( Zeng et al, 2018 ) have been characterized. There are different preventive control methods practiced against these root rot fungi, but truly curative methods are urgently needed.…”
Section: Introductionmentioning
confidence: 99%